Copper alloy strip and production process thereof

By adding Zr-Ti alloy powder, Y-Al composite and modified graphite micropowder to the copper alloy and adopting multi-process processing, the problem of insufficient mechanical properties of traditional copper alloy strips is solved, and the tensile strength, hardness, toughness and wear rate of copper alloy strips are significantly improved, and it is suitable for environments with high temperature, high pressure and frequent mechanical friction.

CN119506637BActive Publication Date: 2025-04-08国工恒昌新材料(义乌)有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510066739.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-08
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional copper alloy strips are difficult to meet the rigorous needs of modern industry in terms of tensile strength, hardness, toughness and wear rate, especially in environments of high temperature, high pressure and frequent mechanical friction, which show high wear rate and insufficient toughness.

Method used

Copper alloy strips with excellent mechanical properties were prepared by adding Zr-Ti alloy powder, Y-Al composite and modified graphite micropowder to the copper alloy, and vacuum drying, hot pressing treatment, cold isostatic pressure, sintering and hot rolling.

Benefits of technology

It significantly improves the tensile strength, hardness, toughness and wear rate of copper alloy strips, and can maintain good performance under complex stress environments and extreme temperature conditions, extend the service life of parts and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506637B_ABST
    Figure CN119506637B_ABST
Patent Text Reader

Abstract

The present invention discloses a copper alloy strip and a production process thereof, comprising the following steps: S1, batching, S2, raw material pretreatment, S3, powder mixing, S4, pressing and forming, S5, sintering, S6, hot rolling, S7, cold rolling, S8, annealing; and also discloses a copper alloy strip prepared by the production process of the above copper alloy strip. The present invention can effectively change the mechanical properties of the copper matrix, refine the organizational grains, and further improve the mechanical properties of the copper alloy strip, such as tensile strength, hardness, toughness and wear rate, by adding Zr-Ti alloy powder, Y-Al composite and modified graphite powder to the copper alloy; in the process of preparing the Y-Al composite, stirring is performed under ultrasonic oscillation conditions, thereby further improving the modified preparation effect of the Y-Al composite, and further balancing the mechanical properties, such as tensile strength, hardness, toughness and wear rate, between the copper alloy strips.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper alloy strips, in particular to a copper alloy strip and a production process thereof. Background Art

[0002] In the rapid development of modern industry, copper alloy strips, as a key basic material, are widely used in many fields such as electronics, automobiles, aerospace, etc., and their performance directly affects the quality and performance of related products. However, traditional copper alloy strips are gradually unable to meet the increasingly stringent industrial needs in terms of tensile strength, hardness, toughness and wear rate.

[0003] As electronic devices develop towards miniaturization and high performance, copper alloy strips used for electronic component connection and heat dissipation are required not only to have good conductivity, but also to have higher strength and hardness to ensure structural stability and reliability, while maintaining a certain toughness to prevent breakage during processing and use. The mechanical properties of traditional copper alloy strips can no longer meet these requirements.

[0004] In the field of automobile manufacturing, engine parts and transmission systems need to withstand high temperatures, high pressures and frequent mechanical friction, which poses higher challenges to the heat resistance, wear resistance and mechanical properties of copper alloy strips. Existing copper alloy strips have a high wear rate, resulting in a short service life of parts and components, which increases the maintenance cost and energy consumption of automobiles.

[0005] The aerospace field has extremely high requirements on the performance of materials. Copper alloy strips are required to have high strength and hardness while maintaining good toughness and low wear rate in complex stress environments and extreme temperature conditions to ensure the safety and reliability of aircraft. However, the comprehensive performance of traditional copper alloy strips is far from meeting these standards.

[0006] In summary, the development of a new type of copper alloy strip with excellent tensile strength, hardness, toughness and low wear rate has urgent practical significance and broad market prospects to meet the demand for high-performance copper alloy strips in various industrial fields and promote the technological upgrading and development of related industries. Summary of the invention

[0007] The object of the present invention is to provide a copper alloy strip and a production process thereof to solve the problems raised in the above background technology.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A production process for a copper alloy strip comprises the following steps:

[0010] S1. Ingredients: 5-8wt% Zr-Ti alloy powder, 3-5wt% Y-Al compound, 1-2wt% modified graphite powder, and the balance copper powder and inevitable trace impurities are selected according to weight percentage;

[0011] Zr and Ti elements can form fine dispersed phases in the copper matrix, effectively hindering dislocation movement, thereby improving the strength and hardness of the alloy while maintaining a certain toughness; the elements have the effect of refining grains, and the Al element can form a strengthening phase with copper. The two work synergistically to further improve the mechanical properties of the alloy, and improve its heat resistance and oxidation resistance; graphite has good lubricity and self-lubricating properties, which can reduce the friction coefficient of the alloy during processing and use, improve its wear resistance, and do not significantly reduce the strength of the alloy;

[0012] S2. Raw material pretreatment:

[0013] Place the Zr-Ti alloy powder in a vacuum drying oven and dry it at 120-150°C for 4-6 hours to remove moisture and adsorbed gas in the powder to ensure its purity and activity;

[0014] The Y-Al composite is dried in a forced air drying oven at 100-130°C for 3-5 hours to reduce its moisture content to less than 0.1% to prevent pore defects caused by moisture evaporation during subsequent processing;

[0015] The modified graphite powder is dried in a drying oven at 80-100°C for 2-4 hours to ensure its dry state for uniform mixing;

[0016] S3. Powder mixing: Weigh the pretreated Zr-Ti alloy powder, Y-Al composite, modified graphite powder and copper powder according to the designed proportion, put them into a three-dimensional mixer, stir them for 20-30 minutes under nitrogen protection to make them evenly mixed, and then hot-press the mixture in a vacuum hot pressing furnace at a temperature of 400-500°C and a pressure of 20-30MPa. The heat preservation and pressure holding time is 1-2 hours. In order to further improve the mixing uniformity, the machine can be stopped every 1 hour, the mixed powder can be turned over, and then the mixing can be continued.

[0017] S4, pressing and molding: the mixed powder is loaded into a mold and pressed and molded by cold isostatic pressing process, the pressure is controlled at 200-300MPa, the pressure holding time is 1-2 minutes, the pressure increase rate is 5-10MPa / second, and the pressure relief rate is 3-5MPa / second, so that the powder body has a certain density and strength, providing a good foundation for subsequent sintering processing;

[0018] S5. Sintering: The pressed green body is placed in a vacuum sintering furnace for sintering. The sintering temperature is set at 850-950°C, the heating rate is controlled at 10-15°C / min, the holding time is 2-3 hours, and the vacuum degree in the furnace is maintained at 10 -3 -10 -4 Pa; make the powder particles fully metallurgically bonded to form a dense alloy structure. During the insulation period, the state of the blank can be observed through the observation window of the furnace body or the monitoring system to ensure that no abnormal situation occurs.

[0019] S6. Hot rolling: The sintered alloy billet is hot rolled, the heating temperature is controlled at 700-800°C, the heating rate is 8-12°C / min, the hot rolling pass reduction rate is controlled at 20%-30%, and the rolling speed is 3-5 m / s;

[0020] S7. Cold rolling: After hot rolling, the strip is pickled to remove the surface oxide scale and then cold rolled. The total cold rolling reduction rate is controlled at 30%-50%, the cold rolling pass reduction rate is 10%-15%, and the rolling speed is 2-4 m / s. At the same time, the rolling process parameters should be reasonably adjusted according to the thickness and dimensional accuracy requirements of the strip to ensure the flatness and plate shape of the strip.

[0021] S8, annealing treatment: the cold-rolled strip is annealed, the annealing temperature is set at 400-500°C, the heating rate is 5-8°C / min, the holding time is 1-2 hours, the furnace cooling method is adopted, and the cooling rate is 3-5°C / min.

[0022] As a further solution of the present invention: the preparation method of the Zr-Ti alloy powder is: zirconium and titanium metal raw materials are smelted in a vacuum arc furnace according to a predetermined ratio to form a Zr-Ti alloy ingot, and then the ingot is subjected to mechanical crushing and ball milling to form an alloy powder with a particle size of 10-50 μm; the ball milling process is carried out under an argon protective atmosphere, the ball-to-material ratio is 4:1, the ball mill speed is controlled at 250-350 rpm, and the ball milling time is 4-6 hours.

[0023] As a further scheme of the present invention: the preparation method of the Y-Al complex is: yttrium nitrate and aluminum powder are added to deionized water in a stoichiometric ratio, heated to 80-90°C under stirring conditions, reacted for 1-2 hours to generate yttrium hydroxide precipitate and aluminum ion solution, and then after filtering and washing, the yttrium hydroxide precipitate and aluminum powder are calcined in a high-temperature furnace at 600-700°C for 2-3 hours to allow the two to fully react to form a Y-Al complex, and the complex is ground into a powder with a particle size of less than 30μm for use.

[0024] As a further scheme of the present invention: the preparation method of modified graphite micropowder is: adding graphite micropowder to an ethanol solution containing a coupling agent, the mass ratio of graphite micropowder to coupling agent is 10:1, stirring for 30-45 minutes under ultrasonic oscillation conditions to allow the coupling agent to be fully adsorbed on the surface of the graphite micropowder, and then drying the mixture at 80-100°C for 2-3 hours to obtain modified graphite micropowder.

[0025] As a further solution of the present invention: the coupling agent is KH550 organosilane coupling agent.

[0026] As a further solution of the present invention: in S5, after the insulation is completed, the heating is stopped and the furnace body is allowed to cool naturally to 400-500°C, and the cooling rate is controlled at 8-12°C / minute. When the furnace temperature drops to 400-500°C, the cooling fan is turned on to accelerate the cooling speed of the furnace body until the furnace temperature drops below 100°C.

[0027] As a further solution of the present invention: In S7, the pickling process is: using a sulfuric acid solution with a concentration of 10%-15% as the pickling medium, the pickling temperature is controlled at 40-60°C, and the pickling time is 5-10 minutes. During the pickling process, the acid solution should be continuously stirred to ensure that the oxide scale on the surface of the strip can be fully removed. At the same time, care should be taken to prevent the occurrence of over-pickling. After pickling, the strip is rinsed with clean water until the pH value of the rinse water reaches 6-7, and then dried at a temperature of 80-100°C for 3-5 minutes.

[0028] As a further solution of the present invention: in S7, a cold rolling lubricant is used in the cold rolling process, the concentration of the lubricant is 5%-8%, and the flow rate is 5-10 liters / minute.

[0029] The present invention provides a copper alloy strip, which is produced by adopting the above method.

[0030] The copper alloy strip comprises the following components in percentage by weight: 5-8wt% Zr-Ti alloy powder, 3-5wt% Y-Al compound, 1-2wt% modified graphite powder, and the remainder copper powder and inevitable trace impurities.

[0031] The tensile strength of the copper alloy strip is ≥420MPa, and the Vickers hardness of the copper alloy strip is 160-200HV.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1. The present invention can effectively change the mechanical properties of the copper matrix, refine the microstructure grains, and further improve the mechanical properties of the copper alloy strip, such as tensile strength, hardness, toughness, and wear rate, by adding Zr-Ti alloy powder, Y-Al composite, and modified graphite powder to the copper alloy;

[0034] 2. In the process of preparing the Y-Al composite, the present invention further improves the modification preparation effect of the Y-Al composite by stirring under ultrasonic oscillation conditions, and further balances the mechanical properties such as tensile strength, hardness, toughness and wear rate between the copper alloy strips. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a metallographic diagram with a scale ratio of 1:200um in an embodiment of the present invention.

[0036] Figure 2 This is a metallographic diagram with a scale ratio of 1:20 um in an embodiment of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Embodiment 1: In the embodiment of the present invention, a production process of a copper alloy strip comprises the following steps:

[0039] S1. Ingredients: 6.5wt% Zr-Ti alloy powder, 4wt% Y-Al composite, 1.5wt% modified graphite powder, and the balance copper powder and inevitable trace impurities are selected according to weight percentage;

[0040] The preparation method of the Zr-Ti alloy powder is as follows: smelting zirconium and titanium metal raw materials in a vacuum arc furnace according to a predetermined ratio to prepare a Zr-Ti alloy ingot, and then subjecting the ingot to mechanical crushing and ball milling to prepare an alloy powder with a particle size of 30 μm; the ball milling process is carried out under an argon protective atmosphere, the ball-to-material ratio is 4:1, the ball mill speed is controlled at 300 rpm, and the ball milling time is 5 hours;

[0041] The preparation method of the Y-Al composite is as follows: yttrium nitrate and aluminum powder are added to deionized water according to a stoichiometric ratio, heated to 85°C under stirring conditions, reacted for 1.5 hours to generate yttrium hydroxide precipitate and aluminum ion solution, filtered and washed, and then calcined the yttrium hydroxide precipitate and aluminum powder in a high-temperature furnace at 650°C for 2.5 hours to allow the two to fully react to form a Y-Al composite, and the composite is ground into a powder with a particle size of less than 30 μm for standby use;

[0042] The preparation method of the modified graphite powder is as follows: adding the graphite powder to an ethanol solution containing a coupling agent, wherein the coupling agent is a KH550 organic silane coupling agent, and the mass ratio of the graphite powder to the coupling agent is 10:1; stirring for 35.5 minutes under ultrasonic oscillation conditions to allow the coupling agent to be fully adsorbed on the surface of the graphite powder; and then drying the mixture at 90° C. for 2.5 hours to obtain the modified graphite powder;

[0043] S2. Raw material pretreatment:

[0044] The Zr-Ti alloy powder was placed in a vacuum drying oven and dried at 135°C for 5 hours to remove moisture and adsorbed gas in the powder;

[0045] The Y-Al composite was dried in a forced air drying oven at 115 °C for 4 h to a moisture content of less than 0.1%;

[0046] The modified graphite powder was dried in a drying oven at 90°C for 3 hours to ensure its dry state for easy uniform mixing;

[0047] S3, powder mixing: weigh the pretreated Zr-Ti alloy powder, Y-Al composite, modified graphite powder and copper powder according to the designed proportion, put them into a three-dimensional mixer, stir them for 25 minutes under nitrogen protection to make them evenly mixed, and then perform hot pressing treatment on the mixture in a vacuum hot pressing furnace, the hot pressing temperature is 450°C, the pressure is 25MPa, and the heat preservation and pressure holding time is 1.5 hours;

[0048] S4, pressing and molding: the mixed powder is loaded into a mold and pressed and molded by cold isostatic pressing process, the pressure is controlled at 250MPa, the pressure holding time is 1.5 minutes, the pressure increase rate is 7.5MPa / second, and the pressure relief rate is 4MPa / second;

[0049] S5. Sintering: The pressed green body is placed in a vacuum sintering furnace for sintering. The sintering temperature is set at 900°C, the heating rate is controlled at 12.5°C / min, the holding time is 2.5 hours, and the vacuum degree in the furnace is maintained at 5.5*10 -4 Pa; After the insulation is completed, stop heating and let the furnace body cool naturally to 450°C. The cooling rate is controlled at 10°C / minute. When the furnace temperature drops to 450°C, turn on the cooling fan to speed up the cooling speed of the furnace body until the furnace temperature drops below 100°C;

[0050] S6. Hot rolling: The sintered alloy billet is hot rolled, the heating temperature is controlled at 750°C, the heating rate is 10°C / min, the hot rolling pass reduction rate is controlled at 25%, and the rolling speed is 4 m / s;

[0051] S7. Cold rolling: After the hot-rolled strip is pickled to remove the surface oxide scale, it is cold rolled. The total cold rolling reduction rate is controlled at 40%, the cold rolling pass reduction rate is 12.5%, and the rolling speed is 3 m / s. The pickling process is: a sulfuric acid solution with a concentration of 12.5% ​​is used as the pickling medium, the pickling temperature is controlled at 50°C, and the pickling time is 7.5 minutes. During the pickling process, the acid solution must be continuously stirred to ensure that the oxide scale on the surface of the strip can be fully removed. At the same time, care must be taken to prevent over-pickling. After pickling, the strip is rinsed with clean water until the pH value of the rinse water reaches 6.5, and then dried at 90°C for 4 minutes. A cold rolling lubricant is used in the cold rolling process, and the lubricant concentration is 6.5% and the flow rate is 7.5 liters / minute.

[0052] S8, annealing treatment: the cold-rolled strip is annealed, the annealing temperature is set at 450°C, the heating rate is 6.5°C / min, the holding time is 1.5 hours, the furnace cooling method is adopted, and the cooling rate is 4°C / min.

[0053] Embodiment 2: This embodiment differs from Embodiment 1 in that, in step S1, 5wt% Zr-Ti alloy powder, 3wt% Y-Al composite, 1wt% modified graphite powder, and the remainder copper powder and inevitable trace impurities are selected by weight percentage.

[0054] Embodiment 3: This embodiment differs from Embodiment 1 in that, in step S1, 8wt% Zr-Ti alloy powder, 5wt% Y-Al composite, 2wt% modified graphite powder, and the remainder copper powder and inevitable trace impurities are selected by weight percentage.

[0055] Embodiment 4: This embodiment is different from Embodiment 1 in that, in the step S1, the method for preparing the Zr-Ti alloy powder is as follows: zirconium and titanium metal raw materials are smelted in a vacuum arc furnace according to a predetermined ratio to form a Zr-Ti alloy ingot, and then the ingot is subjected to mechanical crushing and ball milling to form an alloy powder with a particle size of 50 μm; the ball milling process is carried out under an argon protective atmosphere, the ball-to-material ratio is 4:1, the ball mill speed is controlled at 250 rpm, and the ball milling time is 4 hours;

[0056] The preparation method of the Y-Al composite is as follows: yttrium nitrate and aluminum powder are added to deionized water according to a stoichiometric ratio, heated to 80°C under stirring conditions, reacted for 1 hour to generate yttrium hydroxide precipitate and aluminum ion solution, and then filtered and washed, and the yttrium hydroxide precipitate and aluminum powder are calcined at 600°C in a high-temperature furnace for 2 hours to allow the two to fully react to form a Y-Al composite, and the composite is ground into a powder with a particle size of less than 30 μm for standby use;

[0057] The preparation method of modified graphite micropowder is as follows: adding graphite micropowder to an ethanol solution containing a coupling agent, wherein the coupling agent is KH550 organosilane coupling agent, and the mass ratio of graphite micropowder to coupling agent is 10:1; stirring for 30 minutes under ultrasonic oscillation conditions to allow the coupling agent to be fully adsorbed on the surface of the graphite micropowder; and then drying the mixture at 80°C for 2 hours to obtain modified graphite micropowder.

[0058] Embodiment 5: This embodiment is different from Embodiment 1 in that, in the step S1, the preparation method of the Zr-Ti alloy powder is as follows: zirconium and titanium metal raw materials are smelted in a vacuum arc furnace according to a predetermined ratio to form a Zr-Ti alloy ingot, and then the ingot is subjected to mechanical crushing and ball milling to form an alloy powder with a particle size of 10; the ball milling process is carried out under an argon protective atmosphere, the ball-to-material ratio is 4:1, the ball mill speed is controlled at 350rpm, and the ball milling time is 6 hours;

[0059] The preparation method of the Y-Al composite is as follows: yttrium nitrate and aluminum powder are added to deionized water according to a stoichiometric ratio, heated to 90°C under stirring conditions, reacted for 2 hours to generate yttrium hydroxide precipitate and aluminum ion solution, filtered and washed, and then calcined the yttrium hydroxide precipitate and aluminum powder in a high-temperature furnace at 700°C for 3 hours to allow the two to fully react to form a Y-Al composite, and the composite is ground into a powder with a particle size of less than 30 μm for standby use;

[0060] The preparation method of modified graphite micropowder is as follows: adding graphite micropowder to an ethanol solution containing a coupling agent, wherein the coupling agent is KH550 organosilane coupling agent, and the mass ratio of graphite micropowder to coupling agent is 10:1; stirring for 45 minutes under ultrasonic oscillation conditions to allow the coupling agent to be fully adsorbed on the surface of the graphite micropowder; and then drying the mixture at 100°C for 3 hours to obtain modified graphite micropowder.

[0061] Embodiment 6: This embodiment differs from Embodiment 1 in that, in step S2, the raw materials are pretreated:

[0062] The Zr-Ti alloy powder was placed in a vacuum drying oven and dried at 120°C for 4 hours to remove moisture and adsorbed gas in the powder;

[0063] The Y-Al composite was dried in a forced air drying oven at 100 °C for 3 h to a moisture content of less than 0.1%;

[0064] The modified graphite powder was dried in a drying oven at 80°C for 2 hours to ensure its dry state for easy uniform mixing.

[0065] Embodiment 7: This embodiment differs from Embodiment 1 in that, in step S2, the raw materials are pretreated:

[0066] The Zr-Ti alloy powder was placed in a vacuum drying oven and dried at 150°C for 6 hours to remove moisture and adsorbed gas in the powder;

[0067] The Y-Al composite was dried in a forced air drying oven at 130 °C for 5 h to a moisture content of less than 0.1%;

[0068] The modified graphite powder was dried in a drying oven at 100°C for 4 hours to ensure its dry state for easy uniform mixing.

[0069] Example 8: The difference between this example and Example 1 is that, in step S3, the powders are mixed: the pretreated Zr-Ti alloy powder, Y-Al composite, modified graphite powder and copper powder are weighed according to the designed proportion, put into a three-dimensional mixer, and stirred for 20 minutes under nitrogen protection to mix them evenly. Then the mixture is hot-pressed in a vacuum hot pressing furnace. The hot pressing temperature is 400°C, the pressure is 20 MPa, and the insulation time is 1 hour.

[0070] Example 9: The difference between this example and Example 1 is that, in the step S3, the powders are mixed: the pretreated Zr-Ti alloy powder, Y-Al composite, modified graphite powder and copper powder are weighed according to the designed proportion, put into a three-dimensional mixer, and stirred for 30 minutes under nitrogen protection to mix them evenly. Then the mixture is hot-pressed in a vacuum hot pressing furnace. The hot pressing temperature is 500°C, the pressure is 30 MPa, and the insulation time is 2 hours.

[0071] Example 10: This example differs from Example 1 in that, in step S4, the mixed powder is loaded into a mold and pressed by cold isostatic pressing. The pressure is controlled at 200 MPa, the holding time is 1 minute, the pressure increase rate is 5 MPa / second, and the pressure relief rate is 3 MPa / second.

[0072] Example 11: This example differs from Example 1 in that, in step S4, the mixed powder is loaded into a mold and pressed by cold isostatic pressing. The pressure is controlled at 300 MPa, the holding time is 2 minutes, the pressure increase rate is 10 MPa / second, and the pressure relief rate is 5 MPa / second.

[0073] Example 12: This example is different from Example 1 in that, in step S5, sintering: the pressed green body is placed in a vacuum sintering furnace for sintering, the sintering temperature is set at 850°C, the heating rate is controlled at 10°C / min, the holding time is 2 hours, and the vacuum degree in the furnace is maintained at 10 -3Pa; After the insulation is completed, stop heating and let the furnace body cool naturally to 400℃. The cooling rate is controlled at 8℃ / minute. When the furnace temperature drops to 400℃, turn on the cooling fan to speed up the cooling speed of the furnace body until the furnace temperature drops below 100℃.

[0074] Example 13: This example is different from Example 1 in that, in step S5, sintering: the pressed green body is placed in a vacuum sintering furnace for sintering, the sintering temperature is set at 950°C, the heating rate is controlled at 15°C / min, the holding time is 3 hours, and the vacuum degree in the furnace is maintained at 10 -4 Pa; After the insulation is completed, stop heating and let the furnace body cool naturally to 500℃. The cooling rate is controlled at 12℃ / minute. When the furnace temperature drops to 500℃, turn on the cooling fan to speed up the cooling speed of the furnace body until the furnace temperature drops below 100℃.

[0075] Example 14: The difference between this example and Example 1 is that in step S6, hot rolling processing: the sintered alloy billet is hot rolled, the heating temperature is controlled at 700°C, the heating rate is 8°C / min, the hot rolling pass reduction rate is controlled at 20%, and the rolling speed is 3 m / s.

[0076] Example 15: The difference between this example and Example 1 is that in step S6, hot rolling processing: the sintered alloy billet is hot rolled, the heating temperature is controlled at 800°C, the heating rate is 12°C / min, the hot rolling pass reduction rate is controlled at 30%, and the rolling speed is 5 m / s.

[0077] Example 16: The difference between this example and Example 1 is that in step S7, cold rolling processing: the hot-rolled strip is pickled to remove the surface oxide scale and then cold rolled, the total cold rolling reduction rate is controlled at 30%, the cold rolling pass reduction rate is 10%, and the rolling speed is 2 m / s; the pickling process is: a 10% sulfuric acid solution is used as the pickling medium, the pickling temperature is controlled at 40°C, the pickling time is 5 minutes, the acid solution is constantly stirred during the pickling process to ensure that the oxide scale on the surface of the strip can be fully removed, and at the same time, care should be taken to prevent over-pickling. After pickling, the strip is rinsed with clean water until the pH value of the rinse water reaches 6, and then dried at 80°C for 3 minutes; a cold rolling lubricant is used in the cold rolling process, the concentration of the lubricant is 5%, and the flow rate is 5 liters / minute.

[0078] Example 17: The difference between this example and Example 1 is that in step S7, cold rolling processing: the hot-rolled strip is pickled to remove the surface oxide scale, and then cold rolled, the total cold rolling reduction rate is controlled at 50%, the cold rolling pass reduction rate is 15%, and the rolling speed is 4 m / s; the pickling process is: a 15% sulfuric acid solution is used as the pickling medium, the pickling temperature is controlled at 60°C, the pickling time is 10 minutes, and the acid solution is constantly stirred during the pickling process to ensure that the oxide scale on the surface of the strip can be fully removed. At the same time, care should be taken to prevent over-pickling. After pickling, the strip is rinsed with clean water until the pH value of the rinse water reaches 7, and then dried at a temperature of 100°C and a drying time of 5 minutes; a cold rolling lubricant is used in the cold rolling process, the concentration of the lubricant is 8%, and the flow rate is 10 liters / minute.

[0079] Example 18: The difference between this example and Example 1 is that in step S8, annealing treatment: the cold-rolled strip is annealed, the annealing temperature is set at 400°C, the heating rate is 5°C / min, the holding time is 1 hour, and the furnace cooling method is adopted, and the cooling rate is 3°C / min.

[0080] Example 19: The difference between this example and Example 1 is that in step S8, annealing treatment: the cold-rolled strip is annealed, the annealing temperature is set at 500°C, the heating rate is 8°C / min, the holding time is 2 hours, and the furnace cooling method is adopted, and the cooling rate is 5°C / min.

[0081] Comparative Example 1: This embodiment is different from Embodiment 1 in that, in step S1, the ingredients do not contain Zr-Ti alloy powder.

[0082] Comparative Example 2: This embodiment is different from Embodiment 1 in that, in step S1, the ingredients do not contain Y-Al composite.

[0083] Comparative Example 3: This embodiment is different from Embodiment 1 in that, in step S1, the ingredients do not contain modified graphite powder.

[0084] Comparative Example 4: This embodiment is different from Embodiment 5 in that, in the step S1, the preparation method of the Y-Al composite is stirred for 45 minutes in a conventional stirring manner without stirring under ultrasonic oscillation conditions.

[0085] Mechanical properties experimental test methods

[0086] Tensile strength test: Use a universal material testing machine and perform the test according to the standard tensile test method (such as ASTM E8). The tensile rate is controlled at 0.5-1mm / min until the sample breaks. Record the maximum tensile force at break and calculate the tensile strength using the formula.

[0087] Vickers hardness test: Use a Vickers hardness tester to apply a certain load (such as 5kg) to the surface of the sample and maintain it for a certain time (such as 10s), measure the diagonal length of the indentation, and calculate the Vickers hardness value according to the formula.

[0088] Fracture toughness KIC test: A pre-cracked specimen is used for a three-point bending test. The fracture toughness KIC value is calculated using the relevant formula based on the load-displacement curve recorded during the test.

[0089] Wear rate test: Using a pin-on-disc wear tester, the sample and the mating disk are subjected to friction and wear tests under a certain load (such as 50N) and rotation speed (such as 200rpm). After a certain wear time (such as 30min), the wear amount of the sample is measured and the wear rate is calculated using the formula.

[0090] The corresponding mechanical property tests were performed on the copper alloy strips prepared by the production processes of the above-mentioned Examples 1-19 and Comparative Examples 1-4, and the results are shown in Table 1 below.

[0091] The copper alloy strip prepared in Example 1 was subjected to metallographic examination to obtain Figure 1 , Figure 2 The scales shown are 1:200um and 1:20um respectively. Figure 1 , Figure 2 It can be observed that the copper alloy strip prepared by the method of the present invention has finer grains, higher density and better performance:

[0092] Table 1

[0093]

[0094] From Table 1, we can conclude that:

[0095] Conclusion 1: Combining Examples 1-19, it can be concluded that Example 1 is better in comprehensive performance because its various preparation process parameters are within a more appropriate range, which can better synergistically improve the various properties of the alloy, thereby achieving a better balance between ensuring better tensile strength, hardness, toughness and wear rate.

[0096] Conclusion 2: Based on Comparative Examples 1-3, it is concluded that:

[0097] In terms of tensile strength, due to the lack of Zr-Ti alloy powder, its dispersion strengthening effect is lost, and the hindrance to dislocation movement is reduced, making the tensile strength significantly lower than that of Example 1. In the tensile test, the material is more susceptible to plastic deformation and fracture. Without the Y-Al composite, the precipitation strengthening phase cannot be formed, and the dislocation cannot be effectively pinned, resulting in a tensile strength lower than that of Example 1. Although the lack of modified graphite powder has a relatively small effect on the tensile strength, its absence may affect the synergistic effect between other components to a certain extent, still resulting in a tensile strength lower than that of Example 1.

[0098] In terms of Vickers hardness, Zr-Ti alloy powder helps to form a compact crystal structure. Its absence will make the crystal structure relatively loose, reduce the hardness, and more easily produce larger indentations in the hardness test, which is lower than Example 1. The lack of Y-Al composite results in the inability to form a strengthening phase to increase the compactness of the crystal, and the hardness decreases, which is lower than Example 1. The modified graphite powder itself contributes to the hardness to a certain extent. Without it, the hardness will be reduced, but this effect is smaller than the previous two, and is still lower than Example 1.

[0099] In terms of the fracture toughness value KIC, the lack of Zr-Ti alloy powder will weaken the grain refinement and dislocation barrier effect of the alloy, and the cracks will be more likely to expand when subjected to stress. The toughness is significantly lower than that of Example 1. The Y-Al composite plays an important role in refining grains and enhancing interface bonding. Without it, the toughness will decrease, which is lower than that of Example 1. Although the modified graphite powder has a certain auxiliary effect on toughness, its absence has a relatively small effect on the anti-fracture toughness, but the toughness is still lower than that of Example 1.

[0100] In terms of wear rate, the absence of Zr-Ti alloy powder will reduce the hardness of the alloy and may affect the synergistic effect of other components, making it easier to wear during the wear process, and the wear rate is higher than that of Example 1. The lack of Y-Al composite leads to a decrease in hardness and changes in organizational structure, which reduces wear resistance and the wear rate is higher than that of Example 1. In the absence of modified graphite powder, the self-lubricating property is lost, the friction coefficient increases, and the wear rate is significantly higher than that of Example 1.

[0101] Conclusion 3: In combination with Example 5 and Comparative 4, in the preparation method of Y-Al composite, ultrasonic oscillation stirring has an important influence on the performance of the alloy. It can promote uniform mixing of components, thereby improving the comprehensive properties of the alloy such as tensile strength, hardness, toughness and wear resistance.

[0102] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0103] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A production process for a copper alloy strip, characterized in that: The steps include: S1. Ingredients: 5-8wt% Zr-Ti alloy powder, 3-5wt% Y-Al compound, 1-2wt% modified graphite powder, and the balance copper powder and inevitable trace impurities are selected according to weight percentage; The preparation method of the Zr-Ti alloy powder is as follows: zirconium and titanium metal raw materials are smelted in a vacuum arc furnace according to a predetermined ratio to prepare a Zr-Ti alloy ingot, and then the ingot is subjected to mechanical crushing and ball milling to prepare an alloy powder with a particle size of 10-50 μm; the ball milling process is carried out under an argon protective atmosphere, the ball-to-material ratio is 4:1, the ball mill speed is controlled at 250-350 rpm, and the ball milling time is 4-6 hours; The preparation method of the Y-Al composite is as follows: yttrium nitrate and aluminum powder are added to deionized water according to a stoichiometric ratio, heated to 80-90° C. under stirring conditions, reacted for 1-2 hours to generate yttrium hydroxide precipitate and aluminum ion solution, filtered and washed, and then calcined the yttrium hydroxide precipitate and aluminum powder in a high-temperature furnace at 600-700° C. for 2-3 hours to allow the two to fully react to form a Y-Al composite, and the composite is ground into a powder with a particle size of less than 30 μm for standby use; The preparation method of modified graphite micropowder is as follows: adding graphite micropowder to an ethanol solution containing a coupling agent, wherein the mass ratio of graphite micropowder to coupling agent is 10:1, stirring for 30-45 minutes under ultrasonic oscillation conditions to allow the coupling agent to be fully adsorbed on the surface of the graphite micropowder, and then drying the mixture at 80-100° C. for 2-3 hours to obtain modified graphite micropowder; S2. Raw material pretreatment: Place the Zr-Ti alloy powder in a vacuum drying oven and dry it at 120-150°C for 4-6 hours to remove moisture and adsorbed gas in the powder; The Y-Al composite is dried in a forced air drying oven at 100-130° C. for 3-5 hours to reduce its moisture content to less than 0.1%; The modified graphite powder is dried in a drying oven at 80-100°C for 2-4 hours to ensure its dry state for uniform mixing; S3, powder mixing: weigh the pretreated Zr-Ti alloy powder, Y-Al composite, modified graphite powder and copper powder according to the designed proportion, put them into a three-dimensional mixer, stir them for 20-30 minutes under nitrogen protection to make them evenly mixed, and then perform hot pressing treatment on the mixture in a vacuum hot pressing furnace, the hot pressing temperature is 400-500°C, the pressure is 20-30MPa, and the heat preservation and pressure holding time is 1-2 hours; S4, pressing and molding: the mixed powder is loaded into a mold and pressed and molded by cold isostatic pressing process, the pressure is controlled at 200-300MPa, the pressure holding time is 1-2 minutes, the pressure increase rate is 5-10MPa / second, and the pressure relief rate is 3-5MPa / second; S5. Sintering: The pressed green body is placed in a vacuum sintering furnace for sintering. The sintering temperature is set at 850-950°C, the heating rate is controlled at 10-15°C / min, the holding time is 2-3 hours, and the vacuum degree in the furnace is maintained at 10 -3 -10 -4 Pa; S6. Hot rolling: The sintered alloy billet is hot rolled, the heating temperature is controlled at 700-800°C, the heating rate is 8-12°C / min, the hot rolling pass reduction rate is controlled at 20%-30%, and the rolling speed is 3-5 m / s; S7, cold rolling: the hot-rolled strip is pickled to remove the surface oxide scale, and then cold rolled. The total cold rolling reduction rate is controlled at 30%-50%, the cold rolling pass reduction rate is 10%-15%, and the rolling speed is 2-4 m / s; S8, annealing treatment: the cold-rolled strip is annealed, the annealing temperature is set at 400-500°C, the heating rate is 5-8°C / min, the holding time is 1-2 hours, the furnace cooling method is adopted, and the cooling rate is 3-5°C / min.

2. The production process of a copper alloy strip according to claim 1, characterized in that: The coupling agent is KH550 organic silane coupling agent.

3. The production process of a copper alloy strip according to claim 1, characterized in that: In S5, after the insulation is completed, the heating is stopped and the furnace body is allowed to cool naturally to 400-500°C, and the cooling rate is controlled at 8-12°C / minute. When the furnace temperature drops to 400-500°C, the cooling fan is turned on to accelerate the cooling speed of the furnace body until the furnace temperature drops below 100°C.

4. The production process of a copper alloy strip according to claim 1, characterized in that: In S7, the pickling process is: using a sulfuric acid solution with a concentration of 10%-15% as the pickling medium, the pickling temperature is controlled at 40-60°C, the pickling time is 5-10 minutes, and the acid solution is continuously stirred during the pickling process to ensure that the oxide scale on the surface of the strip can be fully removed. At the same time, attention should be paid to prevent the occurrence of over-pickling. After pickling, rinse the strip with clean water until the pH value of the rinse water reaches 6-7, and then dry it at a drying temperature of 80-100°C and a drying time of 3-5 minutes.

5. The production process of a copper alloy strip according to claim 1, characterized in that: In S7, a cold rolling lubricant is used in the cold rolling process, the concentration of the lubricant is 5%-8%, and the flow rate is 5-10 liters / minute.

6. A copper alloy strip produced by the production process according to any one of claims 1 to 5.

7. The copper alloy strip according to claim 6, wherein the tensile strength of the copper alloy strip is ≥420 MPa, and the Vickers hardness of the copper alloy strip is 160-200 HV.

Citation Information

Patent Citations

  • Dispersed copper composite material and preparation method thereof

    CN105132736A

  • Preparation method of copper alloy / graphite composite material

    CN115181871A